Pelatihan Kewirausahaan dan UMKM Digital untuk Pemuda Menuju Kemandirian Ekonomi di Desa Karang Kemiri, Kecamatan Belitang, Kabupaten OKU Timur - Akhsanul Huda; Widodo Widodo; Lia Rahmawati (Jurnal Pengabdian Kepada Masyarakat, 2025)
Village youth play a strategic role in driving locally-based economic development. However, challenges include limited entrepreneurial skills and minimal use of digital technology in managing MSMEs. This community service activity aims to improve the knowledge, skills, and motivation of youth in Karang Kemiri Village, Belitang District, East OKU Regency, in the areas of entrepreneurship and digital MSMEs. The community service method is implemented through participatory training, hands-on digital marketing practice, and business mentoring. The results of the activity indicate a significant increase in understanding of entrepreneurial concepts, skills in using social media as a promotional tool, and the emergence of youth initiatives to start businesses based on local products. Therefore, this training is an effective strategy to encourage economic independence among village youth.